2023
DOI: 10.1590/2317-1545v45268562
|View full text |Cite
|
Sign up to set email alerts
|

Importance of the lignin content in the pod wall and seed coat on soybean seed physiological and health performances

Abstract: The effects of lignin on soybean seed quality have been studied since the early 1990s. Initially, higher lignin content in the seed coat was associated with greater resistance to mechanical damage by the seeds. Later, positive relationships of lignin content in the seed coat were associated with tolerance to stresses caused by weathering in pre-harvest, resulting in improved seed quality. Additional studies have shown that higher lignin content in the pod wall of soybean is also related to production of seeds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…PFCW: Protein-free cell wall França-Neto et al (1999). andKrzyzanowski et al (2023) detected a greater amount of lignin in dark-colored seed coats, since they have around 12.18% more lignin compared to the 4.75% found in yellow seeds.…”
mentioning
confidence: 87%
“…PFCW: Protein-free cell wall França-Neto et al (1999). andKrzyzanowski et al (2023) detected a greater amount of lignin in dark-colored seed coats, since they have around 12.18% more lignin compared to the 4.75% found in yellow seeds.…”
mentioning
confidence: 87%
“…Krzyzanowski et al [14] reviewed the importance of lignin to soybean seed quality and highlighted that (i) high lignin contents in the soybean pod wall and seed coat are related to seeds with high physical, sanitary and physiological parameters; (ii) coloredcoat soybean seeds (black or brown) have a higher seed quality due to their higher lignin content and the presence of anthocyanin; and (iii) boron presents an inverse relationship with lignin content.…”
Section: Figurementioning
confidence: 99%
“…Interestingly, optical and scanning microscopy revealed lignin deposits in the testa of soybean seeds and palisade cell walls (Menezes et al, 2009). In this way, soybean genotypes with higher lignin content in the tegument have better physical and physiological qualities and greater resistance to mechanical damage (Krzyzanowski et al, 2023). Consistent with this, a relevant study using the pendulum test (Carbonell and Krzyzanowski, 1995) showed a direct relationship between seed coat lignin and the resistance index, classifying 12 field-grown soybean cultivars as resistant, moderately resistant, and susceptible to mechanical damage.…”
Section: Introductionmentioning
confidence: 97%
“…Soybean seed is a complex structure composed of three main parts: the coat or tegument, cotyledon, and embryonic axis. The tegument, a dead layer, plays a crucial role in seed quality, protecting it against adverse weather, pests, and mechanical damage (Krzyzanowski et al, 2023). High rainfall and humidity oscillations associated with high temperatures can cause damage to the seed coat and result in significant losses during seed production (França-Neto et al, 2016).…”
Section: Introductionmentioning
confidence: 99%